(3eOGQc GdCMcGe aj TQM TQGFY GdESdGes - (3GdYGedj, GdehShj, GdLYHj, eMeO Hf Ydj Hf MSjf, J (B1009 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3cJGH GdUdGI , GdUdGI dZI GdOYGA bGd GdLhgQj (B: (3hGdUdGI ef Gddg GdQMeI hGdUdGI hGOI GdUdhGJ GdeaQhVGJ , haj fgGjI GHf GdCKjQ PcQ dgG eYGfj efgG CfgG GdYHGOI GdeNUhUI hGdXf Cf gPG GdeYfi djS HMbjbI dZI dCf Cgd GddZI (B...s
(3BNQgG (B:s
..... (3hjOd Ydjg QhGjGJ efgG eG QhGg GdTjN aj GdUMjM Yf CHj (B.. (3Yf CHj YHO Gddg Ydjg GdSdGe aj GdQLd jchf Na EeGe aSde bHd GdEeGe bGd djS Ydjg HPdc HCS haj GdUMjM (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\ 507 .s
(3gOjI GdYGQajf (B2\ 264s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis